1997
DOI: 10.1086/204624
|View full text |Cite
|
Sign up to set email alerts
|

Why Polyandry Fails: Sources of Instability in Polyandrous Marriages

Abstract: Polyandry has long been viewed as an anomalous form of marriage that raises fundamental questions about variability in human kinship systems. This paper integrates and evaluates a set of hypotheses derived from sociocultural anthropological and evolutionary biological theories of polyandry against data collected on the Nyinba, a well-studied ethnically Tibetan population living in northwestern Nepal. In this population, polyandry is fraternal; it is the normative form of marriage and highly valued culturally. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…But the problem with the insurance argument based on high male productivity is that in the South American groups who practice partible paternity, Walker et al (2010) found that male food production is not nearly as calorically important as it is among high-latitude foragers. Levine and Silk (1997) note that polyandry in classical societies is a less stable marital form than monogamy or polygyny, owing to male sexual jealousy. Senior husbands attempt to restrict sexual access of junior husbands, and mounting dissatisfaction of junior husbands leads them to leave when new marital prospects materialize.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the problem with the insurance argument based on high male productivity is that in the South American groups who practice partible paternity, Walker et al (2010) found that male food production is not nearly as calorically important as it is among high-latitude foragers. Levine and Silk (1997) note that polyandry in classical societies is a less stable marital form than monogamy or polygyny, owing to male sexual jealousy. Senior husbands attempt to restrict sexual access of junior husbands, and mounting dissatisfaction of junior husbands leads them to leave when new marital prospects materialize.…”
Section: Discussionmentioning
confidence: 99%
“…Many have argued (e.g., Levine and Silk 1997) that polyandrous unions are unstable. We could not find sufficient data on this variable in the sources we consulted.…”
Section: Methodsmentioning
confidence: 99%
“…The assumption of enormous adaptability has also been challenged by many anthropologists (see Brown 1990 for overview) concerned with the topics of reproduction and family intimacy. For example, some (Ekvall 1968;Levine and Silk 1997) find that the fraternal polyandrous marriage system is unstable largely due to sexual and emotional factors, rather than economic considerations. Research on co-wife relationships in polygynous families find them to be emotionally unsatisfactory forthe majority of participants (Al-Krenawi 1999;Al-Krenawi and Graham 1999;Chisholm and Burbank 1991;Hill and Hurtado 1996; Jankowiak 200 l;Meekers and Franklin 1995;Strassman 1997;Ware 1980), However, other researchers (Borgerhoff-Mulder 1992Kilbride 1994;Madhavan 2002;Mason 1982) report that under certain circumstances, women living in a polygynous family system enjoy material and emotional satisfaction.…”
mentioning
confidence: 99%
“…Broadly, this phenomenon is viewed as a response to peculiar social and/or ecological conditions, such as an unbalanced sex ratio leading to severe scarcity of marriageable men or a circumscribed, harsh ecology requiring the pooling of male labor (see reviews in Levine and Silk, 1997;Starkweather and Hames, 2012). Broadly, this phenomenon is viewed as a response to peculiar social and/or ecological conditions, such as an unbalanced sex ratio leading to severe scarcity of marriageable men or a circumscribed, harsh ecology requiring the pooling of male labor (see reviews in Levine and Silk, 1997;Starkweather and Hames, 2012).…”
Section: Polyandrous Marriage As a Response To Environmental Challengesmentioning
confidence: 99%